Magneto Immunoassays for Plasmodium falciparum Histidine-Rich Protein 2 Related to Malaria based on Magnetic Nanoparticles - de Souza Castilho, M. [UNESP]; Laube, T.; Yamanaka, Hideko [UNESP]; Alegret, S.; Pividori, M. I. (Amer Chemical Soc, 2011)
Magneto immunoassay-based strategies for the detection of Plasmodium falciparum histidine-rich protein 2 (HRP2) related to malaria are described for the first time by using magnetic micro- and nanoparticles. The covalent immobilization of a commercial monoclonal antibody toward the HRP2 protein in magnetic beads and nanoparticles was evaluated and compared. The immunological reaction for the protein HRP2 was successfully performed in a sandwich assay on magnetic micro- and nanoparticles by using a second monoclonal antibody labeled with the enzyme, horseradish peroxidase (HRP). Then, the modified magnetic particles were easily captured by a magneto sensor made of graphite-epoxy composite (m-GEC) which was also used as the transducer for the electrochemical detection. The performance of the immunoassay-based strategy with the electrochemical magneto immunosensors was successfully evaluated and compared with a novel magneto-ELISA based on optical detection using spiked serum samples. Improved sensitivity was obtained when using 300 nm magnetic nanoparticles in both cases. The electrochemical magneto immunosensor coupled with magnetic nanoparticles have shown better analytical performance in terms of limit of detection (0.36 ng ML(-1)), which is much lower than the LOD reported by other methods. Moreover, at a low level of HRP2 concentration of 31.0 ng mL(-1), a signal of 15.30 mu A was reached with a cutoff value of 0.34 mu A, giving a clear positive result with a non-specific adsorption ratio of 51. Due to the high sensitivity, this novel strategy offers great promise for rapid, simple, cost-effective, and on-site detection of falciparum malaria disease in patients, but also to screen out at-risk blood samples for prevention of transfusion-transmitted malaria.